Concussion history in rugby union players is associated with depressed cerebrovascular reactivity and cognition - Owens, T. S.; Calverley, T. A.; Stacey, B. S.; Rose, G.; Fall, L.; Tsukamoto, H.; Jones, G.; Corkill, R.; Tuaillon, E.; Hirtz, C.; Lehmann, S.; Marchi, N.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Recurrent contact and concussion in rugby union remains a significant public health concern given the potential increased risk of neurodegeneration in later life. This study determined to what extent prior-recurrent contact impacts molecular-hemodynamic biomarkers underpinning cognition in current professional rugby union players with a history of concussion. Measurements were performed in 20 professional rugby union players with an average of 16 (interquartile range [IQR] 13-19) years playing history reporting 3 (IQR 1-4) concussions. They were compared to 17 sex-age-physical activity-and education-matched non-contact controls with no prior history of self-reported concussion. Venous blood was assayed directly for the ascorbate free radical (A•- electron paramagnetic resonance spectroscopy) nitric oxide metabolites (NO reductive ozone-based chemiluminescence) and select biomarkers of neurovascular unit integrity (NVU chemiluminescence/ELISA). Middle cerebral artery blood flow velocity (MCAv doppler ultrasound) was employed to determine basal perfusion and cerebrovascular reactivity (CVR) to hyper/hypocapnia (CVRCO2range). Cognition was assessed by neuropsychometric testing. Elevated systemic oxidative-nitrosative stress was confirmed in the players through increased A•- (p < 0.001) and suppression of NO bioavailability (p < 0.001). This was accompanied by a lower CVR range (CVRCO2range; p = 0.045) elevation in neurofilament light-chain (p = 0.010) and frontotemporal impairments in immediate-memory (p = 0.001) delayed-recall (p = 0.048) and fine-motor coordination (p < 0.001). Accelerated cognitive decline subsequent to prior-recurrent contact and concussion history is associated with a free radical-mediated suppression of CVR and neuronal injury providing important mechanistic insight that may help better inform clinical management.